SIMULASI ANTRIAN PASIEN RAWAT INAP UNTUK MENGURANGI WAITING LIST VIP DI RUMAH SAKIT - Frylie Frescia Falen; Subagyo Subagyo (Jurnal Teknosains, 2018)
Inefficiency of service and the waiting time can occur in inpatient services, especially in VIP rooms. Reduction in waiting lists for patients entering the VIP room is carried out by increasing the bed capacity and the allocation of health workers. The study was conducted by modeling the service system in hospitalization, which began from the patient service at the Emergency Room (IGD) until service in the VIP room of a hospital in Sukabumi. The model was built with 2 scenarios, scenario 1 was designed to improve the performance of the IGD by adding beds and health workers so that patients had an alternative choice in class 1 before getting service in the VIP room, and scenario 2 was designed by not changing the system in the emergency room, but adding 10 VIP rooms. Scenario 2 is a solution and can visually improve the VIP service system by reducing the waiting time by 50.55 hours, with the investment value of net present value (NPV) > 0 and internal rate of return (IRR) 32.2%, against the Minimum Attractive Rate of Return (MARR) 12% per year profitable. Scenario 2 by adding 10 VIP rooms, initially 25 units to 35 units, effectively being able to produce improvements in significantly reducing the waiting list originally from 50.94 hours to 39 minutes there was a decrease (99.23%), and could reduce the utility level or busyness of service in VIP was originally 93.49% to 87.19%. From the results of NPV analysis > 0, and IRR 32.2% assuming MARR 12% per year, constructing 10 VIP rooms in 5 years can give a profit of 20.2% per year. Scenario 2 can be used as the basis for hospitals in making inpatient service system policies, especially in VIP rooms.